Al-Kazimina Al-Ghaiz Sebagai Satu Bentuk Self Regulation: Studi Komparatif Antara Ilmu Tafsir Dan Ilmu Psikologi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
The development of information technology and social media in the digital era has brought various challenges in emotional management, particularly related to increasing social conflict, cyberbullying, and psychological pressure. The ability to control emotions is an important aspect of maintaining mental health and building harmonious social relations. In Islam, the concept of emotional control is reflected in the term al-kazimina al-ghaiz found in QS. Ali Imran verse 134. This study aims to analyze the meaning of al-kazimina al-ghaiz according to M. Quraish Shihab’s interpretation in Tafsir Al-Misbah and to examine its relevance to the concept of self regulation in modern psychology. This research uses a library research method with a thematic interpretation (maudhu’i) approach by examining relevant tafsir literature, psychological theories, and scientific articles. The findings show that al-kazimina al-ghaiz does not merely mean suppressing anger, but reflects the conscious ability to control emotions so that they are not expressed in harmful behavior. This concept is in line with self regulation and emotion regulation theories, yet it has a broader dimension because it includes psychological, moral, and spiritual aspects through anger control, forgiveness, and ihsan.